Preoperative Point-of-Care Ultrasound to Identify Frailty and Predict Postoperative Outcomes: A Diagnostic Accuracy Study. (1st December 2021) - Canales, Cecilia; Mazor, Einat; Coy, Heidi; Grogan, Tristan R.; Duval, Victor; Raman, Steven; Cannesson, Maxime; Singh, Sumit P.
Abstract : Background: Frailty is increasingly being recognized as a public health issue, straining healthcare resources and increasing costs to care for these patients. Frailty is the decline in physical and cognitive reserves leading to increased vulnerability to stressors such as surgery or disease states. The goal of this pilot diagnostic accuracy study was to identify whether point-of-care ultrasound measurements of the quadriceps and rectus femoris muscles can be used to discriminate between frail and not-frail patients and predict postoperative outcomes. This study hypothesized that ultrasound could discriminate between frail and not-frail patients before surgery. Methods: Preoperative ultrasound measurements of the quadriceps and rectus femoris were obtained in patients with previous computed tomography scans. Using the computed tomography scans, psoas muscle area was measured in all patients for comparative purposes. Frailty was identified using the Fried phenotype assessment. Postoperative outcomes included unplanned intensive care unit admission, delirium, intensive care unit length of stay, hospital length of stay, unplanned skilled nursing facility admission, rehospitalization, falls within 30 days, and all-cause 30-day and 1-yr mortality. Results: A total of 32 patients and 20 healthy volunteers were included. Frailty was identified in 18 of the 32 patients. Receiver operating characteristic curve analysis showed that quadriceps depth and psoas muscle area are able to identify frailty (area under the curve–receiver operating characteristic, 0.80 [95% CI, 0.64 to 0.97] and 0.88 [95% CI, 0.76 to 1.00], respectively), whereas the cross-sectional area of the rectus femoris is less promising (area under the curve–receiver operating characteristic, 0.70 [95% CI, 0.49 to 0.91]). Quadriceps depth was also associated with unplanned postoperative skilled nursing facility discharge disposition (area under the curve 0.81 [95% CI, 0.61 to 1.00]) and delirium (area under the curve 0.89 [95% CI, 0.77 to 1.00]). Conclusions: Similar to computed tomography measurements of psoas muscle area, preoperative ultrasound measurements of quadriceps depth shows promise in discriminating between frail and not-frail patients before surgery. It was also associated with skilled nursing facility admission and postoperative delirium. Abstract : Quadriceps depth defined using point-of-care ultrasound was able to predict frailty (defined using the Fried phenotype assessment) with good discrimination. Quadriceps depth was also a predictor of certain adverse postoperative outcomes including discharge to a skilled nursing facility and delirium. Additional studies with larger samples of patients are needed to confirm the clinical utility of this approach and determine whether these associations are independent of potential confounders such as surgery type.